Konsep Kebebasan Menurut Will Kymlicka - Solilit, Fidelis (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
This article talks about Will Kymlicka's concept of freedom. It should be noted that the emergence of Kymlicka's idea of freedom is inseparable from his big theme of "Multiculturalism". Kymlicka defines multiculturalism so that everyone must be treated properly by looking at their rights, because everyone has freedom both individually and in groups that are reflected in culture. For this reason, the most basic thing emphasized by Kymlicka is freedom. What kind of freedom does she offer? Kymlicka divides freedom into liberalism and individual freedom. As well as freedom in the context of culture. Therefore, I see that in reality everyone, be it from ethnicity, race, and so on, has the same rights. Free to express their opinions without any pressure from any party or group. The emergence of this concept was caused by the injustice experienced by Canadian society at that time. The issue raised is how Kymlicka strives for equality in everyone individually, as well as in groups. This means that everyone must receive the same treatment without discriminating between one group and another. Freedom means that there is an attitude of acceptance within each individual. The author will discuss why Will Kymlicka sees freedom as one of the most concerned ideas, in impacting the cultures of each ethnic group, race and so on.Abstrak:Artikel ini berbicara mengenai konsep kebebasan Will Kymlicka. Perlu diketahui bahwa munculnya gagasan kebebasan dari Kymlicka tidak terlepas dari tema besarnya “Multikulturalisme”. Kymlicka mendefinisikan multikulturalisme agar setiap orang harus diperlakuan layak dengan melihat pada hak-haknya, karena setiap orang memiliki kebebasan baik secara individu maupun kelompok yang tercermin dalam kebudayaan. Untuk itu, hal yang paling dasar ditenkankan oleh Kymlicka mengenai   keebebasan. Kebebsan seperti apa yang ditawarkan olehnya? Kymlicka membagi kebabesan menjadi, kebebasan liberalisme dan kebebasan individu. Serta kebebasan dalam konteks kebudayaan. Oleh karena itu, saya melihat pada kenyataanya setiap orang baik itu dari suku, etnis, ras, dan sebagainya, mempunyai hak yang sama. Bebas mengungkapkan pendapat tanpa ada tekanan dari pihak atau golongan mana pun. Munculnya konsep ini, disebabkan oleh ketidakadilan yang dialami oleh masyarakat Kanada saat itu. Persoalan yang diangkat adalah bagaimana Kymlicka mengupayakan agar ada kesetaraan dalam diri setiap orang yang secara individu, maupun kelompok. Artinya, setiap orang harus mendapat perlakuan yang sama tanpa membeda-bedakan kelompok yang satu dengan kelompok yang lain. Kebebasan dimaksudkan adanya sikap penerimaan dalam diri setiap individu. Penulis akan membahas mengapa Will Kymlicka melihat kebebasan sebagai salah satu gagasan yang sangat diperhatikan, dalam memberikan dampak bagi kebudayaan-kebudayaan dari setiap kelompok etnis, ras dan sebagainya.